PENGARUH KONDISI EKONOMI TERHADAP TINGKAT PENDIDIKAN ANAK DI DESA SINAR TEBUDAK KECAMATAN TUJUH BELAS - Nurhayati, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to find out the economic condition and educational level of children in the Village Sinar Tebudak District Tujuh Belas. The economic condition of equal to 81,93% included in low category and education level of child 45,78% in low category with equation Y = -2,303 + 0,803 X. The method used in this research is descriptive method with research form study relationship. Then, the populations in this study were parent of farm families in the village of Sinar Tebudak District Tujuh Belas amounting to 508 families with the sample used amounted to 83 families. Data collection techniques in this study used direct technique, indirect technique and documentary study technique. Meanwhile, to analyze the data of the researcher used the formula with SPSS version 22.0 statistic program with the result of data analysis stated that there is influence between the economic condition of the child education level is 36.1% with the coefficient of determination is 0,601 (R) with R square 0,361 and level Interpretation of strong relationships.Keyword: Economic Condition, Child Education Level.